2007
DOI: 10.1017/s0022149x07799121
|View full text |Cite
|
Sign up to set email alerts
|

Light and confocal microscopic observations of adultSchistosoma mansonifrom mice fed on a high-fat diet

Abstract: The morphological aspects of Schistosoma mansoni adult worms recovered from albino mice fed on a cholesterol-rich diet compared to mice fed on a standard chow were investigated. After feeding on their respective diets for over a period of 5 months, mice were subcutaneously infected with c. 50 S. mansoni cercariae/mouse. Blood samples were obtained 1 day prior to experimental infections and 63 days later, when mice were euthanized by jugular section (hypovolaemic shock). Total cholesterol (TC) levels were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…These data suggest that schistosomes are closely associated with the modulation of host lipid metabolism (El Ridi et al 2004, Tallima & El Ridi 2005. The most plausible explanation is the presence of signalling pathways by which parasites detect host signals and respond to them in a way that presumably both increases their survival (Loverde et al 2007) and reproduction of adult worms (Neves et al 2007a). In this study, regression and linear correlation between faecal eggs and worm pairs found no correlation in the IHFC group.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…These data suggest that schistosomes are closely associated with the modulation of host lipid metabolism (El Ridi et al 2004, Tallima & El Ridi 2005. The most plausible explanation is the presence of signalling pathways by which parasites detect host signals and respond to them in a way that presumably both increases their survival (Loverde et al 2007) and reproduction of adult worms (Neves et al 2007a). In this study, regression and linear correlation between faecal eggs and worm pairs found no correlation in the IHFC group.…”
Section: Discussionmentioning
confidence: 49%
“…Chronic exposure to schistosome eggs promoted the development of a Th2 response and reduced the levels of total cholesterol and LDL in serum, but it failed to reduce aortic lesion development (La Flamme et al 2007). As part of a series of studies being carried out in our laboratories on the role of dyslipidaemia during acute schistosomiasis infection, it was observed that a high-fat diet favours the development of adult worms (Neves et al 2007a). Moreover, egg maturity, faecal output, viability and egg hatching were higher compared to mice fed a standard diet (Neves et al 2007b).…”
mentioning
confidence: 99%
“…A proposed scale was (−) not detected, (±) rare, (+) mild, (++) moderate, and (+++) intense [38]. Because increased steatosis has been associated with increased fibrosis, I-A may also be helpful in measuring fibrosis [39], mainly if slices are stained by picrosirius red to enhance the collagen fibers [40,41]. The I-A is particularly important if we consider that today images are captured by digital cameras and image handling is done entirely within the computer [42].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged feeding of fat-enriched diets induces hepatic steatosis in rodents (Zhang et al 1999, Rao et al 2001, Picard et al 2002, Buettner et al 2007, Marques et al 2010). During S. mansoni infection, immunocompromised mice fed either a normal diet (Doenhoff et al 1981) or high-fat chow (Neves et al 2007a) developed hepatic steatosis. Alternatively, PR throughout gestation and during the first half of lactation has caused higher rates of hepatic steatosis in six-month-old rats (Souza-Mello et al 2007).…”
Section: Discussionmentioning
confidence: 99%